Pendapatan dan Konsumsi terhadap Kesejahteraan Keluarga Petani Kopi - Darwin Damanik; Erlindo Ficky Nainggolan (IPM2KPE, 2022)
This study aims to analyze the effect of household income and consumption on the welfare of coffee farming families in Salaon Tonga-Tonga Village, Ronggurnihuta District, Samosir Regency partially and simultaneously. The research method used is a quantitative and descriptive method of field research (survey). The type of data used in this study is primary data obtained from the results of a questionnaire of 100 coffee farmer respondents in Salaon Tonga-tonga Village, Ronggurnihuta District, Samosir Regency. The results showed that a) the income variable (X1) partially (individually) has a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency; b) the consumption variable (X2) partially (individuals) has a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency; c) the variable income (X1) and consumption (X2) simultaneously (together) have a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency; d) the coefficient of determination (R Square) in this study is 0.427 (42.70%). This means that 42.70% of the independent variables (income and consumption) can explain variations in the dependent variable (welfare). While 57.30% is explained by other independent variables that are not included in this study. The conclusions in this study are, a) the income variable (X1) partially (individuals) has a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency; b) the consumption variable (X2) partially (individuals) has a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency; c) the variable income (X1) and consumption (X2) simultaneously (together) have a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency. Keywords: Welfare, Consumption, Income, Coffee Farmers